Drug Prevention Education Programs in Schools in High-Risk Areas: Challenges for Primary School Teachers in Malaysia - Ahmad Jazimin Jusoh; Ciptro Handrianto; Durrah Athirah Walid; Suzaily Wahab; Shahid Rasool (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractDrug prevention education programs have been implemented in primary and secondary schools in Malaysia. This study aimed to investigate the existing drug prevention education programs in primary schools in high-risk areas of Perak, Malaysia and to identify the challenges faced by primary school teachers to implement these programs. The methods used in this study was a qualitative case study design by using interviews for data collection. Seven participants, including primary school teachers, a Ministry of Education Malaysia officer, a National Anti-Drug Agency (NADA) Perak officer, and a State of Education Department officer, were involved as study samples. The results of the study showed that teachers still face problems delivering drug messages in the teaching-learning process because they do not have enough learning materials or knowledge. Teachersâ€™ challenges arise not only from the school or educational policy but also from parents` involvement. It can be concluded that the primary school teachers in Malaysia still face challenges related to their skills, community supports, and government policies in drug prevention education programs. It is expected the study can be used by the stakeholders when planning and evaluating drug preventive in Malaysian primary schools especially in selected hot spot areas.Keywords: challenges, drug prevention, high-risk areas, primary school teachers.Â AbstrakProgram pendidikan pencegahan narkoba telah dilaksanakan di sekolah dasar dan menengah di Malaysia. Penelitian ini bertujuan untuk menyelidiki program pendidikan pencegahan narkoba yang ada di sekolah dasar di daerah berisiko tinggi Perak, Malaysia dan untuk mengidentifikasi tantangan yang dihadapi oleh guru sekolah dasar untuk melaksanakan program ini. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan desain studi kasus dengan menggunakan wawancara untuk pengumpulan data. Tujuh peserta, termasuk guru sekolah dasar, petugas Kementerian Pendidikan Malaysia, petugas Badan Anti Narkoba Nasional (NADA) Perak, dan petugas Departemen Pendidikan Negara Bagian, dilibatkan sebagai sampel penelitian. Hasil penelitian menunjukkan bahwa guru masih menghadapi kendala penyampaian pesan narkoba dalam proses belajar mengajar karena tidak memiliki bahan ajar atau pengetahuan yang cukup. Tantangan guru muncul tidak hanya dari sekolah atau kebijakan pendidikan, tetapi juga dari keterlibatan orang tua. Dapat disimpulkan bahwa guru sekolah dasar di Malaysia masih menghadapi tantangan terkait keterampilan mereka, dukungan masyarakat, dan kebijakan pemerintah dalam program pendidikan pencegahan narkoba. Diharapkan penelitian ini dapat digunakan oleh para pemangku kepentingan ketika merencanakan dan mengevaluasi program pencegahan narkoba di sekolah dasar Malaysia, khususnya di daerah yang terpilih.Kata kunci: tantangan, pencegahan narkoba, daerah berisiko tinggi, guru sekolah dasar.